Pengaruh Konseling Kelompok Dengan Pendekatan Solution Focused Brief Counseling (SFBC) Terhadap Peningkatan Komunikasi Interpersonal Santri - Veni Widayanti (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aims to examine the effect of group counseling with a solution focused briefcounseling (SFBC) approach to improving students' interpersonal communication.In this study using the One Group Pretest and Posttest designs, the designused one group of subjects with one type of treatment, namely the experimental group.The population in this study were students of class 2 KMI, amounting to 15 students.Thenumber of samples in this study were 8 students who had low or moderate pretestscores.Determination of sampling using purposive sampling technique, namelydetermination based on predetermined objectives or characteristics. The method ofanalysis in this study used a parametric paired sample t-testThe results of this study indicate that group counseling with a solution focusedbrief counseling (SFBC) approach has an effect on improving students' interpersonalcommunication. This is evidenced by the results of the paired sample t-test with aprobability sig. (2-tailed) 0.001 <0.05. And with the difference in the mean scoreofquestionnaire 23.35% interpersonal communication from the results pretest andposttest. This proves that group counseling with a solution focused brief counseling(SFBC) approach can improve students' interpersonal communication.